The Developmental Sequences of English Negation of Secondary School Students at SMK Putra Bangsa Salatiga and MTs AL Uswah Bergas Semarang Regency - Safitri Mahargiani, Indah; , Prof. Dr. Endang Fauziati, M. Hum; , Muamaroh, Ph.D (2015)
Safitri, Indah M. "Developmental Sequence of English Negation of Secondary School Students at SMK Putra BangsaSalatiga and MTs AL UswahBergas Semarang Regency". Thesis. English Department, Graduate School, Muhammadiyah University, Surakarta. 2015. This research aims to describe the developmental squences of English negation in Junior and Senior high school students: (1). the development of English negation in nominal sentences, (2). the development of English negation in verbal sentences, and (3). The development of English negation in modal auxiliary sentences of secondary school students. The research is largely qualitative and cross-sectional study. This study was conducted in SMK Putra BangsaSalatiga and MTs AL UswahBergas Semarang regency, from December 2014 to February 2015. The object of this research was negative sentences were made by seventh, ninth, tenth, and twelfth grade students of MTs AL UswahBergas and SMK Putra BangsaSalatiga. The data of this research were collected from several techniques including observation, interview, and document analysis. In analyzing qualitative data, the researcher conducted several steps. First, giving a translation test. The students were asked to translate the text in Indonesian to English. The second is to identify the occurrences of negation. The third, the researcher classify and categorize all the data containing negation obtained from all sources. The forth is the researcher interpret and explain the data through the interpretation of the order of developmental language acquisition. The last step is drawing the conclusion. The researcher found that there were three stages of development English negation in each kind of sentences. Nominal sentences: stage one "S + no/not + adjectives/adverb", stage two "S + unanalyzed to be + no/not + adjectives/adverb", and stage three "S + analyzed to be + no/not + adjectives/adverbs". Verbal sentences: stage one "S + no/not + verb", stage two "S + unanalyzed don't + verb", and stage three "S + analyzed don't + verb". Modal auxiliary sentences: stage one "S + no/not + modal + verb", stage two "S + don't + modal + verb", and stage three "S + modal + not (negation) + verb".